Św. Izydor z Sewilli, O dniach, nocy i tygodniu (Etymologiae, V, 30-32: De diebus, de nocte, de hebdomada) - Kaczyńska, Elwira (Vox Patrum, 2022)
The text comprises the author’s commented Polish translation of some chapters of Isidore’s Etymologiae sive Origines (V 30–32), devoted to days, the night and the week.